A questions of vocal-choral preparation at musical-pedagogical faculties - H.M. Martyanova (Academy of Cognitive and Natural Sciences, 2006)
In article some aspects of the contents of professional choir-conductors preparation are considered, namely, the components caused by process of creative self-expression, such professional quality, as musicality, its structure and maintenance of realizatation with a substantial basis of practical activities students of musical-pedagogical faculty is analyzed.